Global Risk of Bacterial Skin Infections and Herpesviridae Infections with Ustekinumab, Secukinumab, and Tumour Necrosis Factor-alpha Inhibitors: Spontaneous Reports of Adverse Drug Reactions from the World Health Organization Pharmacovigilance Center - Linda Davidson; Juul M.P.A. van den Reek; Florence van Hunsel; Elke M.G.J. de Jong; Bart Jan Kullberg (Medical Journals Sweden, 2022)
Genetic defects in interleukin-12/23/17 immunity are associated with an increased risk of Staphylococcus aureus and herpesvirus skin infections. This study analysed spontaneous safety reports from the WHO Pharmacovigilance Center of bacterial skin or herpesvirus infections associated with secukinumab, ustekinumab and tumour necrosis factor-α inhibitors. Associations found in disproportionality analyses were expressed as reporting odds ratios (ROR). For bacterial skin infections, ustekinumab showed the strongest association (ROR 6.09; 95% confidence interval (95% CI) 5.44-6.81), and, among the tumour necrosis factor-α inhibitors, infliximab showed the strongest association (ROR 4.18; 95% CI 3.97-4.40). Risk was comparable between infliximab and secukinumab (ROR 3.51; 95% CI 3.00-4.09). Secukinumab showed the strongest association with herpes simplex infection (ROR 4.80; 95% CI 3.78-6.10). All biologics were equally associated with herpes zoster. Infliximab was the only biologic associated with cytomegalovirus infection (ROR 5.66; 95% CI 5.08-6.31) and had the strongest association with Epstein-Barr virus infection (ROR 6.90; 95% CI 6.03-7.90). All biologics evaluated were positively associated with bacterial skin infections, herpes simplex, and herpes zoster, compared with all other drugs in the WHO database for which individual case safety reports were collected. The possibility of under-reporting, reporting bias and difference in causality assessment between countries and reporters must be taken into account when interpreting the results of disproportionality analyses.